Application of portable measuring equipment in the field of industrial measurement. Issue 1 (July 2021) - Hu, Chang'an; Xing, Rui; Hu, Song; Li, Jiangang
Abstract: With the continuous improvement of measurement requirements, the changing and immovable characteristics of the measured object, the application of portable measuring equipment is gradually increasing. The paper takes the bearing platform, flat plate, industrial robot, fixture, leveling rod verification device and complex system as the typical application cases. This paper presents the multiple applications of three kinds of portable measuring equipment: laser tracker, laser interferometer and joint arm coordinate measuring machine.